The joy of eating: how eating experiences enhance the well-being of older adults - Wang, Xinmin; Qi, Jianwu; Zhang, Kai; Xie, Huiji; Wu, Xingnan (Frontiers in Public Health, 2024)
Introduction The active aging strategy has as its policy implications the health, security, and participation of older people. The joy of eating is the main goal of establishing community-based service facilities for older people, as well as a source of health and well-being and a sense of meaning in the lives of older people. Methods Based on the theory of human-environment relations and cognitive-emotional personality systems (CAPS), the study constructed a structural equation model of the eating experience, nostalgia, place attachment, and the well-being of the older adults in the community canteens as an interactive situation, and explored the relationship between the eating experience and the well-being of older people in the community canteens through the partial least squares structural equation modeling (PLS-SEM). Results The results of the study show that the older adults’ eating experience has a significant positive effect on their well-being, and “eating” can make older adults feel happy. Older adults’ eating experience has a significant effect on nostalgia, place attachment, and well-being, but nostalgia does not have a significant effect on older adults’ well-being, and place attachment in the community canteens can enhance older adults’ well-being. Meanwhile, the study further confirmed that place attachment plays a mediating role in the effect of eating experience on older adults’ well-being. Discussion The findings of the study promote the development of the fields of healthy eating, quality of life assessment, and dietary memory management for older people to a certain extent and provide an important reference for promoting the balanced layout and effective spatial design of community service facilities for older people.